Mid-infrared entangled photon generation in optimised asymmetric semiconductor quantum wells. (February 2016) - Razali, R.; Valavanis, A.; Cooper, J.D.; Ikonić, Z.; Indjin, D.; Harrison, P.
Abstract: The optimal design of asymmetric quantum well structures for generation of entangled photons in the mid-infrared range by spontaneous parametric downconversion is considered, and the efficiency of this process is estimated. Calculations show that a reasonably good degree of entanglement can be obtained, and that the optical interaction length required for optimal conversion is very short, in the few μm range. Highlight: We have optimised quantum well structures to produce large second-order nonlinear susceptibility based on intersubband transitions in the conduction band. The optimization is done using a genetic algorithm. The 3-well quantum structures are good enough to produce high values of the 2nd order nonlinear susceptibility. The required optimal conversion length for the conversion of the pump into entangled photon pairs is very short. Structures which have large spacing between the lower two subbands are advantageous over structures where this spacing is small.